Laser Therapy for Incision Healing in 9 Dogs - Wardlaw, Jennifer L.; Gazzola, Krista M.; Wagoner, Amanda; Brinkman, Erin; Burt, Joey; Butler, Ryan; Gunter, Julie M.; Senter, Lucy H. (Frontiers in Veterinary Science, 2019)
Laser therapy is becoming common place in veterinary medicine with little evidence proving efficacy or dosages. This study evaluated surgical wound healing in canines. Twelve Dachshunds underwent thoraco-lumbar hemilaminectomies for intervertebral disc disease. Digital photographs were taken of their incisions within 24 hours of surgery and 1, 3, 5, 7, and 21 days postoperatively. The first three dogs were used to create a standardized scar scale to score the other dogs’ incision healing. The remaining 9 dogs were randomly assigned to either receive 8 J/cm2 laser therapy once a day for seven days or the non laser treated control group. Incision healing was scored based on the scar scale from 0-5, with zero being a fresh incision and five being completely healed with scar contraction and hair growth. All scar scores significantly improved with increasing time from surgery (<0.001). Good agreement was achieved for inter-rater reliability (p=0.9). Laser therapy increased the scar scale score, showed improved cosmetic healing, by day seven and continued to be significantly increased on day 21 compared to control dogs (p<0.001). Low-level laser therapy daily for 7 days at 8 J/cm2 appears to increase the healing process resulting in a more cosmetic surgical scar.